Occurence of Giardia lamblia in children of municipal day-care centers from Botucatu, São Paulo State, Brazil - Guimarães, Semíramis [UNESP]; Sogayar, Maria Inês L. [UNESP] (Instituto de Medicina Tropical, 1995)
Considering that the number of day-care centers for pre-school-age children has expanded rapidly in developing countries, and that these institutions presenting conditions that facilitate the transmission of many enteric agents, a parasitological survey was carried out in three municipal day-cares from Botucatu: two in the urban area (one in downtown area and the other one in the city periphery area) and the third in the rural area. Three separate stool specimens were collected from 147 children ranging from 0 to 72 months old and 20 staff members. Each stool specimen was processed by Lutz and zinc sulfate flotation methods. The frequency of giardiasis observed among children of downtown, periphery and rural day-cares was 69.6%, 52.7% and 69.6%, respectively. Only one employee was positive for G. lamblia. The examination of three stool specimens increased the positivity for G. lamblia: from the ninety three final positive examinations, 24 (25.5%) and 8 (8.5%) were positives only after examination of the second and third samples, respectively. Others intestinal organisms like Ascaris lumbricoides (20.4%), Trichuris trichiura (19.0%). Hymenolepis nana (8.8%), Entamoeba coli (22.4%) and Blastocystis hominis (32.0%) were frequently found in the children. There was no significant association among localization of the day-cares, sex of the children and the levels of G. lamblia infection. According to the age, G. lamblia was found mainly in children between 12 to 47 months old.

Foi realizado um levantamento parasitológico em três creches da rede municipal: duas na área urbana, uma no centro da cidade e a outra na periferia, e a terceira na zona rural. Três amostras de fezes, coletadas com intervalo de 7 dias, foram obtidas de 147 crianças com idade variando de 0 a 6 anos e de 20 funcionários. Cada amostra foi processada pelos métodos de sedimentação espontânea e centrífugo - flutuação com sulfato de zinco. Os resultados demonstraram que das 147 crianças examinadas, 93 (63,3%) apresentaram cistos de G. lamblia nas fezes. Apenas 1 funcionário foi positivo para G. lamblia. O uso de 3 amostras de fezes aumentou a positividade do exame para o diagnóstico deste parasita, uma vez que dos 93 casos positivos, 24 (25,5%) e 8 (8,5%) foram diagnosticados somente após exame da segunda e terceira amostras, respectivamente. Outros parasitas e comensais intestinais como Ascaris lumbricoides (20,4%), Trichuris trichiura (19,0%), Hymenolepis nana (8,8%), Entamoeba coli (22,4%) e Blastocystis hominis (32,0%) foram diagnosticados. A análise estatística revelou não haver associação entre localização das creches, sexo e a frequência de infecção por G. lamblia. As porcentagens mais altas de infecção por Giardia foram observadas entre as crianças com idade variando de 1 a 4 anos.
Ocorrência de Giardia lamblia em crianças atendidas em creches municipais de Botucatu, Estado de São Paulo, Brasil
Keywords: Giardia lamblia; Giardiasis; Day-care centers; Children